2007
DOI: 10.1073/pnas.0701421104
|View full text |Cite
|
Sign up to set email alerts
|

Proline-rich tyrosine kinase 2 regulates osteoprogenitor cells and bone formation, and offers an anabolic treatment approach for osteoporosis

Abstract: Bone is accrued and maintained primarily through the coupled actions of bone-forming osteoblasts and bone-resorbing osteoclasts. Cumulative in vitro studies indicated that proline-rich tyrosine kinase 2 (PYK2) is a positive mediator of osteoclast function and activity. However, our investigation of PYK2؊/؊ mice did not reveal evidence supporting an essential function for PYK2 in osteoclasts either in vivo or in culture. We find that PYK2؊/؊ mice have high bone mass resulting from an unexpected increase in bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
141
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 22 publications
12
141
0
Order By: Relevance
“…We further examined the impact of inhibiting pY397 on the Rac1 activity by treating OECM-1 cells with PF-431396, a highly selective pyrimidine-based inhibitor of FAK. 21 As shown in Figure 3d (right panel), treatment of 1 μM PF-431396 caused decreases in the levels of pY397 and Rac1-GTP as compared with the vehicle control. Coordinating with the changes in Rac1 activity, expression of Y397F mutant or treatment of PF-431396 led to inhibited cell migration and invasion (Figures 3e and f).…”
Section: Modulation Of Fak Expression and Activity Regulates The Actimentioning
confidence: 70%
“…We further examined the impact of inhibiting pY397 on the Rac1 activity by treating OECM-1 cells with PF-431396, a highly selective pyrimidine-based inhibitor of FAK. 21 As shown in Figure 3d (right panel), treatment of 1 μM PF-431396 caused decreases in the levels of pY397 and Rac1-GTP as compared with the vehicle control. Coordinating with the changes in Rac1 activity, expression of Y397F mutant or treatment of PF-431396 led to inhibited cell migration and invasion (Figures 3e and f).…”
Section: Modulation Of Fak Expression and Activity Regulates The Actimentioning
confidence: 70%
“…Another example is inhibition of the proline-rich tyrosine kinase 2 (PYK2 or PTK2B), a non-receptor tyrosine kinase expressed in bone cells. PYK2-deficient mice show high bone mass and increased MSC differentiation and bone formation, and inhibition of PYK2 was shown to prevent bone loss in OVX rats (125). It can also be considered to inhibit midkine, a heparin-binding growth factor, because midkine deficiency results in increased trabecular bone formation in mice (126).…”
Section: Other Potential Targets For Anabolic Therapiesmentioning
confidence: 99%
“…The focal adhesion tyrosine kinases Pyk2 and FAK are linked to the proliferation, migration, and activity of a variety of mesenchymal, epithelial, and hematopoietic cell types (7)(8)(9)(10). Our group and others have reported that deletion of the Pyk2 gene in mice leads to an increase in bone mass, which is due to defects in the activity of OBs and osteoclasts (7,11).…”
mentioning
confidence: 99%